Experimental analysis on turning of AISI 4340 steel using non-textured, dimple textured and MoS2 coated dimple textured carbide cutting inserts at the rack surface. (2020) - Vignesh, G.; Barik, Debabrata; Ragupathi, P.; Aravind, S.
Abstract: Forming of dimple texture patterns on the rack surface of titanium coated carbide cutting inserts will produce a positive impact on tribological alterations at the cutting insert-workpiece and cutting insert-chip interfaces. The aim of this research is to identify the effect of MoS2 coated and uncoated dimple textured carbide cutting inserts compared to non-textured cutting inserts during dry machining of the AISI 4340 steel. Straight-line patterns of spherical dimples with various diameter, depth, and density ratio were fabricated on the rack face of the cutting insert using the laser marking method. The responses of cutting insert wear at the cutting insert – chip interface, cutting temperature generated during machining and surface quality of the machined surface are analyzed experimentally. Experimental results show that there is a positive influence on machinability and cutting insert wear decreased by about 10% on optimizing the dimple diameter of 90 µm and the depth of 60 µm. Optimizing the dimple diameter and depth plays a significant role in the dimple texturing forming of the carbide insert.